'Mental Workouts for Couch Potatoes': Executive Function Variation among Spanish–English Bilingual Young Adults. (10th October 2017) - Smith, Sara Ashley; Briggs, Jessica G; Pothier, Holly; Garcia, Jorge Nicholas
Abstract: Research has yet to reach a definitive consensus on whether or how bilingualism confers benefits on Executive Function (EF): numerous studies show an EF advantage for bilinguals over monolinguals, while others indicate no significant differences. These inconsistencies demonstrate that the mechanisms behind a potential bilingualism-to-EF relationship remain unclear. Multiple factors likely impact EF outcomes among bilinguals, including proficiency and extent and type and environment of language usage. The current study explored EF skills among a relatively homogeneous sample of 50 Spanish–English bilingual young adults to provide insights into the environmental and individual characteristics that contribute to EF diversity. Hierarchical regression modeling revealed that more balanced bilingual language usage in specific home-based tasks (particularly TV watching), and higher self-reported ability in Spanish and English significantly predicted higher EF. Results support the developing empirical consensus that greater engagement in dual-language contexts bears a positive relationship to EF. The finding that watching TV with a balanced language ratio has a significant positive relationship to EF opens strong potential opportunities for bilinguals to access EF benefits with minimal effort.